INFLUENCE OF DRY HOT CLIMATE ON CONCRETE WORK TECHNOLOGY - Mukhitdinov M.A; Akhmedov Islambek; Umarov Israel (Journal of new century innovations, 2023)
Abstract. This article examines the challenges of working with concrete in dry-hot climates, characterized by extreme temperatures and low humidity. It highlights the detrimental effects of this environment on concrete's strength, durability, and workability. Additionally, it proposes strategies for mitigating these effects through optimized material selection, concrete mix design, proper curing protocols, and the use of specific additives.